PERTENTANGAN PEMBERIAN PERLINDUNGAN HAK PATEN TERHADAP INVENSI PENGGUNAAN TEKNOLOGI CRISPR-Cas9 PADA GEN MANUSIA - Nur Azizah, Ida (UNES Law Review, 2023)
The TRIP’S Agreement confirms that Member States may exclude certain types of inventions from patentability and may refuse to grant patents on methodological inventions used on humans, including the granting of patents on inventions in the field of biotechnology applied to humans. Indonesia regulates patent protection for biotechnology in the Patent Law, which emphasizes that patents cannot be granted for inventions of biotechnological processes applied to humans. However, with the development of technology, the use of inventions in the field of biotechnology applied to human genes is considered to have great benefits for mankind. Therefore, this research that uses doctrinal-normative methodology through a statute approach will discuss how the TRIP’s Agreement and the Patent Law in Indonesia regulate patents on biotechnology products applied to human genes and the urgency of granting patent protection to biotechnology inventions applied to humans so that it can be known that granting patents to biotechnology inventions applied to humans is prohibited by Indonesian law but given freedom under international law and further research and comprehensive studies need to be done to deal with future trade liberalization flows.